Photorefractive reflection holography compound microscope for MEMS characterization - Ferreira, M. S. [UNESP]; Barbosa, E. A. [UNESP] (My University, 2012)
This work describes a reflection holography microscope setup based on sillenite photorefractive crystals and illuminated by a diode laser. The resulting compound microscope has shown to be suitable for MEMs characterization through holographic interferometry.